2008
DOI: 10.1111/j.1365-2648.2008.04606.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of reflexology: systematic review

Abstract: Title. The efficacy of reflexology: systematic review. Aim. This paper is a report of a systematic review to evaluate the efficacy of reflexology in any condition. Background. Anecdotal evidence has shown potential benefits of reflexology in a variety of health conditions. However, the efficacy of reflexology has yet to be determined. Data sources. Cochrane library, PubMed, MEDLINE, EBM review, ProQuest Medical Bundle and SCOPUS databases were searched using the following medical subject headings or key words:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 33 publications
(50 reference statements)
2
80
1
5
Order By: Relevance
“…[39] In five clinical trials, Wang reported some effects of reflexology compared to general massage. [40] Such differences in results can be attributed to different techniques and reflexology spots on hands. Disagreements of specialists in the field of reflexology are confirmed by Jones et al [30,31] Adib-Hajbaghery et al believed that any kind of massage can have many effects on physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[39] In five clinical trials, Wang reported some effects of reflexology compared to general massage. [40] Such differences in results can be attributed to different techniques and reflexology spots on hands. Disagreements of specialists in the field of reflexology are confirmed by Jones et al [30,31] Adib-Hajbaghery et al believed that any kind of massage can have many effects on physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative therapies is used for decrease disease and pain symptoms with nature's healing power and reinforce body's recuperative power and immune system [4]. As one of these methods, reflexology is commonly used, a non-invasive technique [5]. Reflexology, defined as "a technique that applied with hands on hands, foots and ears which are related to all glands, organs and body parts and helps normalization of body functions" by the International Reflexology Institute [6].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, blood stream fastens and homeostasis of the body provided. In addition, it helps the re-absorption of calcium, lactate, urine acid crystals [5].…”
Section: Introductionmentioning
confidence: 99%
“…By using the heel treatment as the control, an experimentally inert reflexology comparison can be achieved in which nonspecific effects such as the compassion of the therapist, the treatment environment, the act of lying supine, expectation of the receiver, and the relaxing effects of simple foot massage 19,20 would be equally present in both intervention and control. Therefore if the beat-to-beat hemodynamic status of either the liver or spleen organs were measured throughout the intervention and control treatment, and the experiment used reflexology-naive subjects in a randomized, double-blinded repeated measures study design, it should be possible to isolate and detect a specific treatment-related hemodynamic effect on the organ in question; a specific effect that should only be present at some point during the intervention (revealed by real-time measurement of the organ or organs of interest), quite distinct from nonspecific components that should be equally present in both, thereby resolving both the map inconsistency problem and providing a suitably robust experimental control.…”
Section: A Reductionist Solutionmentioning
confidence: 99%